Rasio Platelet dan Sel Darah Putih: Implikasinya dalam Patofisiologi Stroke - Azhar, Hafidz Sirojudhin; Kurniati, Intanri; Pramesona, Bayu Anggileo; Utama, Winda Trijayanthi (Medula, 2024)
Acute ischemic stroke is a leading cause of morbidity and mortality worldwide, significantly impacting patients' quality of life and healthcare systems. Understanding prognostic factors that predict clinical outcomes in acute ischemic stroke patients is crucial, especially with the rising prevalence of risk factors such as hypertension, diabetes, and dyslipidemia. Recent studies have focused on hematological biomarkers, particularly the platelet-to-white blood cell ratio (PWR), which reflects the interaction between immune system components and hemostasis. This literature review examines the prognostic value of PWR in acute ischemic stroke, correlating higher PWR with better clinical outcomes measured by the National Institute of Health Stroke Scale (NIHSS). Lower PWR values have been associated with increased mortality risk within 90 days post-stroke. The dynamics of PWR provide insights into the body's response to ischemia and inflammation, highlighting its potential as a valuable prognostic marker. While PWR shows promise as a prognostic tool, limitations such as individual variability in inflammatory response, timing of measurement, and lack of standardization must be considered. Further research is needed to explore PWR's potential across diverse populations and address existing limitations to enhance its clinical application in managing acute ischemic stroke.